Use of aloe vera in dentistry - Pravin Sundarkar; Ravindra Govindwar; Sanjai B Nyamati; Neeraj Alladwar; Vivek Thombre; Abhishek Soni; Anand Raj (Wolters Kluwer Medknow Publications, 2011)
The aloe vera plant has a long history of healing power. Recently, aloe very has gained some popularity as an active natural product used in the medical and dental field for treating many diseases. It has various miraculous properties like anti-inflammatory, antibacterial, antiviral and antitumor which accelerates wound healing and helps in treating various lesions in oral cavity. Though, there are various indications for its use, more clinical research is required to determine its real efficacy in dentistry. The aloe vera plant, its composition, properties, mechanism of action and clinical uses are briefly reviewed in this article.